Proteolytic activities and safety use of Enterococcus faecalis strains isolated from Turkish White Pickled Cheese and milk samples - BARAN, A; NADAROGLU, H; ÖNEM, H; ADIGÜZEL, MC (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, Enterococcus faecalis proteolytic strains which have the potential to degradation of bovine milk proteins were isolated from Turkish White Pickled Cheeses and milk samples. E. faecalis strains were found to have strong caseinolytic activity. The extracellular protease enzymes produced by E. faecalis strains from 60 different samples were analyzed in the pattern of bands on a stained SDS-PAGE gel. The highest proteolytic activity of E. faecalis isolates were determined at pH 7.0 and 40 ℃ for 24 h. In addition, antimicrobial resistance and the presence of selected virulence genes of isolates were investigated for microbiological safety. These findings further emphasize that the E. faecalis isolates can be effective in the degradation of bovine milk proteins.